THE EFFECT OF SERVICE QUALITY ON SATISFACTION AND LOYALTY VISITORS AT RECREATIONAL PARK SENGKALING UNIVERSITAS MUHAMMADIYAH MALANG - Praharjo, ardik (Manajemen Bisnis, 2020)
Service quality is an important key for service companies because providing good service can have an impact on satisfaction and loyalty. The leaders will continue to try to improve the performance of their business to maintain the company in order to achieve satisfaction that ends in customer loyalty. This study aims to determine the effect of service quality on the satisfaction and loyalty of visitors to the Sengkaling UMM Recreational Park both directly and indirectly. The type of research used is explanatory research with a quantitative approach. The sample used is 112 visitors who have visited at least twice and over 18 years old. The data analysis technique used is descriptive research and using path analysis. The results of this study indicate that service quality has a significant effect on visitor satisfaction and loyalty at Taman Rekreasi Sengkaling UMM.